P-257 Apremilast Prevents Intestinal Inflammation in Colitis Models via Influencing Epithelial Barrier. (February 2017) - Weigmann, Benno; Popp, Vanessa; Neurath, Markus; Horan, Gerald; Schafer, Peter
Abstract : Background: Inflammatory bowel disease (IBD) is comprised of 2 major disorders: ulcerative colitis (UC) and Crohn's disease (CD). In IBD, lamina propria mononuclear cells (LPMC) are critical mediators and play important roles in inflammatory process. The proinflammatory cytokine TNF-alpha has been found to exert biological functions in both inflammatory diseases, but the 2 diseases differ in the production of specific cytokines. Apremilast is currently under investigation in a phase 2 study in ulcerative colitis patients, and is a phosphodiesterase 4 (PDE4) inhibitor indicated for treatment of adults with psoriasis and psoriatic arthritis. Apremilast regulates multiple proinflammatory and anti-inflammatory cytokines, and is able to block TNF-alpha production. Consequently, we investigated the role of apremilast in experimental colitis models for both forms of IBD and analysed the influence to epithelial barrier. Previous work has shown that apremilast can reduce TNF-a production and MMP-3 production in colonic LPMC (Gordon 2009). Methods: We evaluated the activity of Apremilast in both the trinitro benzene sulfonic acid (TNBS)-induced and oxazalone-induced colitis models. Apremilast was effective in reducing inflammation disease severity in the TNBS model (which resembles CD). In addition, we analysed 2 different doses of apremilast in the acute oxazolone colitis model (which resembles UC) and observed a protection from inflammation. The inflammation level was documented by miniendoscopic analysis, in-vivo imaging, MEICS score and histologic scoring. The colon was isolated for histological sections in order to do immunofluorescent staining and lamina propria mononuclear cells (LPMCs) together with splenic T cells were analyzed for cytokine levels by ELISA. Results: Furthermore, analysis of cytokines revealed reduction of TNF-alpha, IFN-gamma, IL-6 and IL-13, which are mainly responsible for inflammation in this colitis model. Surprisingly, IL-9 is also reduced in treated animals as shown by qPCR analysis. Since elevated IL-9 may reduce epithelial barrier function, we then tested the activity of apremilast directly on epithelial cells. Measurement of trans epithelial electric resistance (TEER) of Caco-2 cells incubated with apremilast demonstrated a reduction in barrier function at high concentrations. Finally, we generated spheroids from murine colon stem cells and analysed the effect of apremilast. We could demonstrate that apremilast can inhibit proliferation of the organoids as well as induces pre-apoptosis, which may also contribute to an effect on barrier function. These in vitro data suggest Apremilast has the potential to regulate barrier function via either cytokine-mediated mechanisms or via direct activity on epithelial cells. Conclusions: Taken together, these results demonstrate that Apremilast is effective and has broad antiinflammatory activity in 2 murine models of colitis, and is emerging as a potential novel approach for therapy in ulcerative colitis.